The Value of Emotion in Ancient Chinese Literature and Art (Journal of Global Humanities and Social Sciences, 2025)
With the continuous implementation of the strategic goal of building a big socialist cultural country, the country and the people have begun to attach importance to the artistic value of ancient Chinese literature. However, both ancient languages and poems and songs are mainly about emotions. Therefore, when studying, we should analyze the value of emotion in ancient Chinese literature and art. Taking the value of emotion in ancient Chinese literature and art as an example, this paper analyzes the artistic value of emotion from the related exposition and specific value of emotion, so as to improve the people's awareness of emotion and help them better understand the meaning of ancient Chinese literature and discover its artistic charm.